Réponses

2014-04-06T20:29:07+02:00
8x-3=2x+9                     -x+8=-4x+11                  3x+34=11x+10                  -9x+3=-4x+7
8x-2x=9+3                      -x+4x=11-8                     3x-11x=10-34                  -9x+4x=7-3
6x=12                              3x=3                                -8x=-24                           -5x=4
x=12/6                              x=3/3                                 x=-24/-8                         x=4/-5
x=2                                   x=1                                     x=24/8                          ou
                                                                                     x=3                               x=-0.8